2015
DOI: 10.3171/2014.11.spine14877
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spinal osteotomies on spinal cord tension and dural buckling: a cadaveric study

Abstract: OBJECT The standard surgical release of a tethered cord may result in recurrent scar formation and occasionally be associated with retethering. The application of spinal shortening procedures to this challenging problem potentially can reduce tension on the retethered spinal cord while minimizing the difficulties inherent in traditional lumbosacral detethering revision. Although spinal shortening procedures have proven clinical benefit in patients with a recurrent te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
(30 reference statements)
0
17
0
1
Order By: Relevance
“…With a cadaveric tethered cord study, Grande et al 16) demonstrated that a 15-25 mm thoracolumbar subtraction osteotomy effectively lowered the tension on neural structures. In another cadaveric study by Safain et al 35) , 12-16 mm shortening of vertebral column by posterior osteotomy was optimal for adequate tension relief and the minimization of dural buckling.…”
Section: Spinal Column Shortening : An Alternative To Conventional Rementioning
confidence: 90%
“…With a cadaveric tethered cord study, Grande et al 16) demonstrated that a 15-25 mm thoracolumbar subtraction osteotomy effectively lowered the tension on neural structures. In another cadaveric study by Safain et al 35) , 12-16 mm shortening of vertebral column by posterior osteotomy was optimal for adequate tension relief and the minimization of dural buckling.…”
Section: Spinal Column Shortening : An Alternative To Conventional Rementioning
confidence: 90%
“…7) [42]. Eine Studie von Safain et al [43] am Kadaver-Modell kam zu dem Schluss, dass mit einer spinalen Verkürzung von 12 -16 mm ein geeigneter Kompromiss aus spinal entlastender Verkürzung und Vermeiden einer gesteigerten Dura-(und Myelon-)deformierung erreicht werden kann. Letztendlich muss über das Ausmaß der max.…”
Section: Präventionunclassified
“…eThered cord syndrome is a clinical diagnosis with a constellation of signs and symptoms, including back and leg pain, other sensory changes, leg weakness, foot deformity, scoliosis, and bowel and bladder dysfunction. 9,22,23,26,27,30 The pathophysiology of tethered cord syndrome has been hypothesized to be an abnormal stretch of the spinal cord, leading to altered blood flow and hypoxic stress and subsequent worsened mitochondrial oxidative metabolism and electrophysiological insult. It is assumed that prolonged neuronal dysfunction may lead to structural damage to neuronal perikarya and axons.…”
mentioning
confidence: 99%
“…33 Initial treatment for tethered cord syndrome may involve an untethering procedure, which consists of the surgical release of abnormal attachments between the neural elements, adjacent structures, and scar tissue, releasing excessive tension on the spinal cord. 20,30 While untethering is a well-accepted treatment option for tethered cord syndrome, 5,19,22 recurrent tethering from scar formation, a natural reaction to surgery, is a significant risk. Reported rates of secondary tethered cord syndrome following repair of myelomeningoceles have been estimated to be between 3% and 32%; the incidence of recurrent tethered cord syndrome after surgery for lipomyelomeningocele has been reported to be as high as 40%.…”
mentioning
confidence: 99%
See 1 more Smart Citation